Complicated multidrug-resistant tuberculosis (MDR) in a pediatric patient: Case report - Ticlia-Agreda, José Luis (2022)
Objetive: To describe a pediatric case with initial diagnosis of lymph node tuberculosis (TB) that became multidrug resistant miliar and meningeal tuberculosis (TB-MDR) due to treatment dropout twice. Case report: a 4-year-old boy with initial diagnosis of lymph node tuberculosis who had two episodes of dropout from the sensitive scheme treatment. Three months later, there was evidence of bilateral involvement suggestive of miliary TB. During hospitalization, he developed meningeal tuberculosis and hydrocephalus. Due to the history of treatment dropout, a sensitivity of gastric aspirate study was requested, identifying it as multidrug-resistant TB. He started the EZLfxKmEtoCs treatment scheme and complications management, achieving improvement. Conclusions: Treatment dropout is one of the main causes of drug resistance in tuberculosis and its complications. It is necessary to reinforce the early detection and effective treatment of this infection in children, focusing on the follow-up of cases to avoid treatment dropout and the consequent complications.